REDESAIN WEBSITE OBJEK WISATA KOTA SAWAHLUNTO - DIMAS REGA LEONI, Drs. Syafwan, M.Si., Hendra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
Sawahlunto is a small town in West Sumatera Indonesia. This town has 27.345 Ha an area and 65.787 soul population. This town borders in Eastern part of Sijunjung regency. Sawahlunto is led Mr. Ali Yusuf S.Pt as a mayor of Sawahlunto until 2018 later. At this time , the Sawahlunto town evolves to be unique multi old tourism town until it has been one of the best old town in Indonesia. As along of development Sawahlunto tour, the promotion activity of Sawahlunto tour is limited because it only by local radio and print media advertisement.Website is one of most popular media advertisement at this time. It has the range of space and time is not limited. The specific strategies appropriately is required to get website as effective media in promotion until the promotion website has been success. Sawahlunto has had tourism attraction by it self. But the good design and visual communication principle has not been reached by it. There for, redesign tourism attraction of Sawahlunto is made by purpose to promote and present Sawahlunto town more broadly.The redesign of website as the first adversting media of Sawahlunto town. The by way of supporting media that data of analysis is required through the SWOT analysis. This method is required to strength the and complete the project.